2015
DOI: 10.1007/s40828-015-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Hirao reaction: recent developments

Abstract: Organic molecules containing phosphorus, now, constitute a major branch of chemistry, and offer fascinating possibilities for their structural, synthetic, and mechanistic study as well as promising biological activities. Organophosphorus compounds find numerous potential applications in the areas of industrial, agricultural, and medicinal chemistry. Aryl-and vinyl-phosphonates are an important class of organophosphorus compounds with potential biological relevance. The Hirao reaction offers a way to access the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…To obtain the five-membered vinylphosphonate, we attempted heating of compound 15 [40] with diethylphosphite in the presence of a catalytic amount of NiCl 2 [41], but no conversion was observed. Our efforts to construct a P-C bond with diethylphospite via the Pd-catalyzed Hirao reaction with the conventional or microwave-assisted method [42] also failed. As a result, we finally decided to lithiate [43] the O-methyl derivative 16, as achieved via Fenton reaction in a dimethylsulfoxide/H 2 O 2 /Fe 2+ system [44], followed by treatment with 1.0 eq.…”
Section: Phosphonate Synthesis With Lithiationmentioning
confidence: 99%
“…To obtain the five-membered vinylphosphonate, we attempted heating of compound 15 [40] with diethylphosphite in the presence of a catalytic amount of NiCl 2 [41], but no conversion was observed. Our efforts to construct a P-C bond with diethylphospite via the Pd-catalyzed Hirao reaction with the conventional or microwave-assisted method [42] also failed. As a result, we finally decided to lithiate [43] the O-methyl derivative 16, as achieved via Fenton reaction in a dimethylsulfoxide/H 2 O 2 /Fe 2+ system [44], followed by treatment with 1.0 eq.…”
Section: Phosphonate Synthesis With Lithiationmentioning
confidence: 99%
“…16 Green approaches for making C SP 2-P(vO) bonds are important in synthetic chemistry: for instance, the use of microwave-assisted methodology in the hope of shortening the reaction time. 13,[17][18][19][20][21][22] With the aid of microwave apparatus, Keglevich et al reported catalyst-free, 23 ligand-free 24 and ligand-free/ solvent-free 25,26 conditions for coupling C SP 2-P(vO) bonds. In addition to a recently developed photocatalyst-free (transitionmetal-free) method for making valuable organophosphorus compounds, 27 importantly, Montchamp et al demonstrated that the C SP 2-P(vO) coupling of 2-chloropyrazine was successfully catalysed by 1 mol% of an in situ Pd(OAc) 2 /dppf catalytic system.…”
Section: Introductionmentioning
confidence: 99%